Rational Kinetics Control toward Universal Growth of 2D Vertically Stacked Heterostructures. Issue 27 (16th May 2019) - Li, Fang; Feng, Yexin; Li, Ziwei; Ma, Chao; Qu, Junyu; Wu, Xueping; Li, Dong; Zhang, Xuehong; Yang, Tiefeng; He, Yunqiu; Li, Honglai; Hu, Xuelu; et al.
Abstract: The rational control of the nucleation and growth kinetics to enable the growth of 2D vertical heterostructure remains a great challenge. Here, an in‐depth study is provided toward understanding the growth mechanism of transition metal dichalcogenides (TMDCs) vertical heterostructures in terms of the nucleation and kinetics, where active clusters with a high diffusion barrier will induce the nucleation on top of the TMDC templates to realize vertical heterostructures. Based on this mechanism, in the experiment, through rational control of the metal/chalcogenide ratio in the vapor precursors, effective manipulation of the diffusion barrier of the active clusters and precise control of the heteroepitaxy direction are realized. In this way, a family of vertical TMDCs heterostructures is successfully designed. Optical studies and scanning transmission electron microscopy investigations exhibit that the resulting heterostructures possess atomic sharp interfaces without apparent alloying and defects. This study provides a deep understanding regarding the growth mechanism in terms of the nucleation and kinetics and the robust growth of 2D vertical heterostructures, defining a versatile material platform for fundamental studies and potential device applications. Abstract : The growth mechanism of vertical heterostructures is understood in terms of nucleation and kinetics, where active clusters with a high diffusion barrier promote the nucleation on top of transition metal dichalcogenide templates to realize vertical heterostructures. Benefiting from the efficient control of the diffusion barrier of the active clusters, high‐quality vertical heterostructures with various configurations and compositions are successfully synthesized.